Iran's Security Policy in the Post-Revolutionary Era - Byman, Daniel (RAND Corporation, 2001)
Religion, nationalism, ethnicity, economics, and geopolitics all are important in explaining Iran's goals and tactics in its relationship with the outside world, as are the agendas of key security institutions and the ambitions of their leaders. This report assesses Iran's security policy in light of these factors. It examines broad drivers of Iran's security policy, describes important security institutions, explores decisionmaking, and reviews Iran's relations with key countries. The authors conclude that Iraq is widely recognized as the leading threat to Iran's Islamic regime and Afghanistan is seen as an emerging threat. In contrast, Iran has solid, if not necessarily warm, relations with Syria and established working ties to Pakistan and Russia. Iran's policies toward its neighbors are increasingly prudent: It is trying to calm regional tension and end its isolation, although its policies toward Israel and the United States are often an exception to this policy. Iran's security forces, particularly the regular military, are often voices of restraint, preferring shows of force to overactive confrontations. Finally, Iran's security forces generally respect and follow the wishes of Iran's civilian leadership; conducting rogue operations is rare to nonexistent.